2019
DOI: 10.1080/20009666.2019.1593779
|View full text |Cite
|
Sign up to set email alerts
|

YouTube as a source of patient education in idiopathic pulmonary fibrosis: a media content analysis

Abstract: Purpose: Idiopathic pulmonary fibrosis (IPF) is a common cause of pulmonary fibrosis, with millions of individuals affected in the world. Patients may use multiple resources to educate themselves regarding their illness, including popular social media video hosting site YouTube. We set out to determine the quality of patient education material discussing IPF available on YouTube. Methods: 100 consecutive videos were surveyed for review, of which 59 were included in the final analysis. Three independent blinded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
0
6
0
2
Order By: Relevance
“…The use of video for education has become popular in health [42], in medical anatomy education to improve students' grades [43]. The use of video must consider the quality of the content presented, and adjustments are required so that the information conveyed through the video can be accurate [44]. The footage provides short-term and long-term behavior change; previous studies found that video education effectively maintains smoking cessation.…”
Section: Resultsmentioning
confidence: 99%
“…The use of video for education has become popular in health [42], in medical anatomy education to improve students' grades [43]. The use of video must consider the quality of the content presented, and adjustments are required so that the information conveyed through the video can be accurate [44]. The footage provides short-term and long-term behavior change; previous studies found that video education effectively maintains smoking cessation.…”
Section: Resultsmentioning
confidence: 99%
“…Otros investigadores como Ferhatoglu, Kartal, Ekici y Gurkan ( 2019 Adicionalmente, en buena parte de las investigaciones se complementa la escala DISCERN con otros métodos de evaluación de contenidos, destacando entre ellos el benchmark JAMA y la escala Global Quality Score (GQS), junto con otros métodos adaptados de fuentes reputadas, como el National Institute on Deafness and Other Communication Disorders o la American Thoracic Society y American College of Chest Physicians (Lashari et al, 2019) El benchmark JAMA (Journal of American Medical Association) es una herramienta de investigación que mide la calidad de la información dirigida a pacientes con base en cuatro criterios: 1) autoría; 2) atribución; 3) divulgación; y 4) actualidad. De esta forma, se evalúa si el contenido cumple o no con cada criterio, dando 1 punto en caso afirmativo, 0 si no cumple y siendo 4 la máxima puntuación total (Aydin y Aydin, 2020).…”
Section: Diseño Metodológicounclassified
“…Time constraints in busy clinics pose challenges to providing adequate patient support. Many patients find information on-line that is inaccurate, outdated or misleading [15,16] or would have been better understood if communicated by a clinician than read by the patient alone.…”
Section: What Are the Challenges In Communicating With Patients With Ipf?mentioning
confidence: 99%
“…Time constraints in busy clinics pose challenges to providing adequate patient support. Many patients find information online that is inaccurate, outdated or misleading [ 15 , 16 ], or would have been better understood if communicated by a clinician than read by the patient alone. A significant proportion of patients trying to cope with IPF suffer from anxiety or depression [ 17 19 ] or other forms of psychological distress.…”
Section: What Are the Challenges In Communicating With Patients With Ipf?mentioning
confidence: 99%